Effect of Covid-19 on the Socio-Economic Well-Being of Households in Nigeria - Joy Chinyere Kanu; Emmanuel Busuyi Oguntomi; Babajide A Ajayi (Faculty of Economics, Universitas Sriwijaya, 2022)
This study investigated the effect of COVID-19 on the socio-economic wellbeing of households in Nigeria. The main objective was to investigate the effect of COVID-19 on households' income, employment, expenditure and savings in Ayobo-Ipaja Local Council Development Area of Lagos State, Nigeria. The descriptive nonexperimental qualitative study used structured questionnaire to collect data from men and women of working ages between 25 and 65 in Ayobo-Ipaja. Convenience non-probability random sampling technique was used to select 384 participants. The data were analyzed using frequency, percentage, mean, standard deviation and chi-square test. The chi-square results revealed that COVID-19 outbreak has significant effect on households' income, employment, expenditure, and savings in Ayobo-Ipaja Local Council Development Area of Lagos State, Nigeria. It is recommended that government should intensify policy efforts towards economic growth recovery and poverty alleviation programs for increased social inclusion by creating jobs and providing support for the vulnerable citizens